Assessment of Suicidal Triggers of Depression among Adulthood at Sir Cowasjee Hospital Hyderabad: A Cross Sectional Study - Akhtar, Tasleem; Akhtar, Parveen; Manzoor Syed, Binafsha; Rai, Gobind; Areej, Sana; Mansoor Ul Haq (Indus Journal of Bioscience Research, 2024)
Background: Suicide represents a significant public health issue, resulting in extensive social, economic, and emotional effects; annually Over 800,000 people lose their lives to suicide. with 78% occurring in low- and middle-income nations. The figures surrounding suicide among adolescents are particularly alarming: in 2015, it was the second leading cause of death for people aged 15 to 29 globally (World Health Organization, 2018). Objective: To measure the magnitude of the suicidal triggers associated with depression among adults at Sir Cowasjee Hospital, Hyderabad. Methodology: A descriptive cross sectional study was conducted on 326 patients of depression at Sir Cowasjee Institute of Psychiatric Hospital, Hyderabad. Using simple random sampling. Frequencies and percentages were calculated for categorical variables, suicide crisis inventory questionnaire was transformed into scores, multiple linear regression was run to predict significant suicidal triggers of depression value less than 0.05 was considered significant. Results: Demographic triggers of suicidal ideation among depression patients were Illiteracy, low level of education, urban residency, marital conflicts, cheap labor, challenging own business, low monthly income are the main suicidal triggers among depressed adults. Early detection of depressive symptoms is vital in providing early treatment and prevention of suicide. Conclusion: Suicidal crises have been predominantly affecting the daily life activities of adolescents with depression. Early detection of depressive symptoms is vital in providing early treatment and prevention of suicide. There is a need to develop a comprehensive mental health policy to create awareness and curb this suicidal crisis among adults in order to make them productive assets to society.